This advert makes me cry: Disclosure of emotional response to advertisement on Facebook - Emmanuel Mogaji (Cogent Business & Management, 2016)
As social media is transforming how consumers interact with brands and how brand-related content is consumed, this paper aims to investigate if and how Facebook users express their emotions towards advertisements of brand share on the site. Seven hundred and three comments about the Lloyds 250th Anniversary advertisement on Facebook were analysed as positive, negative or neutral attitude towards the advert. Facebook users found the advertisement emotionally appealing and voluntarily report their emotion of love, pride and in some cases anger. The presence of an iconic image like the black horse and the cover music was found to be emotionally appealing. The background music as well aroused positive emotions and engaging. This study introduces the possibility of analysing Facebook comments on brand content to understand consumers' emotional responses and attitudes to the brand. Managers can explore these opportunities to identify what consumers find interesting in advertisements and how best to develop their creative strategies. It also offers the opportunity to allocate resources better to engage consumers with creative advertisement. Unlike interviews or surveys, this is a pioneering study on measuring emotional responses to advertisement through users' self-report on social media.
Keywords: 650